Strategi Operasional untuk Meningkatkan Pendapatan dan Nilai Tambah Usaha Dodol Buah di PD “X” Kabupaten Garut, Jawa Barat - Babas Bastaman; Ani Suryani; Aris Munandar (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
The purpose of this study is to assess overall operational development strategies of PD''X "in increasing incomes and value added fruit dodol. In particular, this study aims to: (1) study the income earned PD''X "in one bulk manufacturing, (2) study the amount of added value from the PD''X" and the amount of value-added contribution of business income, and distribution, (3) study the relationship between the use of production factors with the resulting production and (4) to formulate business development strategies fruit dodol. The results of the study showed that the income level of cash costs, the company earn the highest revenue from pineapple dodol types of Rp 33,698,406, - per year and for the level of income is the total cost of pineapple dodol Rp 26,193,775, - with a value of revenue/cost (R/C) ratio of 1.12. The ratio of value added amounted pineapple dodol 20.15% in exchange for business owners and 66.60% 33.40% labor, dodo sirsak 18.46% registration in exchange for 63.53% of business owners and labor 36.47 %, while the ratio of value added melons dodol and strawberries are of 20.64% in exchange for business owners and 67.38% 32.62% labor. The use of all raw materials in the production process as a whole has a positive effect. This shows that all factors significantly affect the production process. Based on the analysis of marketing strategies that have been done using internal-external (IE) matrix, the position dodol product development of fruit marketing in quadrant II in the box described as the area grow and build. Strategies that can be done by the company based on weighted strengths, weaknesses, opportunities and threats (SWOT) analysis, is as follows: (1) Maintaining a competitive product prices, (2) Opening distributor/new agents in strategic places, (3) Conducting an effective promotion and efficient, (4) Improve the performance marketing in analyzing market demand, (5) Develop and maintain product quality, (6) Expand and maintain market share was achieved, (7) Maintain the selling price in the market and (8) Improving distribution channels